Composing in critique of Nollywood scoring practices - Oladiran, Adeyemi Solomon (My University, 2021)
As a point of departure, this work considers the construction and creative choicese found in Nollywood film music. This investigation is motivated in part by critique the author has witnessed of this music from outside Nigeria during fifteen years of living and working in the music industry in South Africa. The works of notable film scholars like Gorbman (1987) and Prendergast (1992) profoundly highlight the theoretical and practical functions of music in film. Through these theories and principles, the music of selected Nollywood productions is considered. The compositional commonalities in the style, in the region, and at the period (1930-2015), allow for a theorisation of a shared musical identity since the same resources are at the base of these styles. Using these resources, I present a model for using musical resources found in Nigerian traditional music to compose for Nollywood (as well as cinema more generally) and for the concert stage is presented in both composed and written texts. It is argued that Nigerian music identity can be theorized through the use of these common compositional resources. My accompanying portfolio of compositions for the stage and screen seeks to give practical, creative expression to that whilst also serving as a demonstration of the development of my own compositional voice
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Music to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, 2021